2020
DOI: 10.1080/09540121.2020.1781760
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dyadic coping and dyadic adjustment among HIV-serodiscordant couples

Abstract: Living within an HIV-serodiscordant relationship has been recognized as a stressful experience for both HIV-infected and HIV-uninfected partners. However, no study has examined the association between dyadic coping (DC) and dyadic adjustment of such couples. In this study, we analysed the association between DC (positive, negative, and common DC) and dyadic adjustment (consensus, satisfaction, cohesion) among HIVserodiscordant couples, considering individual and cross-partner effects. This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A moderate to strong association between relationship satisfaction and dyadic coping was identified in a meta-analytic review of 39 studies (Falconier & Kuhn, 2019 ). This association has also been identified among heterosexual couples coping with health concerns such as cancer, infertility, and organ transplants (e.g., Badr et al, 2010 ; Molgora et al, 2019 ; Tkachenko et al, 2019 ; Van Schoors et al, 2019 ) and similar findings have been identified among partnered SMM in the realm of HIV-related health (Gamarel & Revenson, 2015 ; Martins et al, 2020 ) and non-HIV health concerns (Randall et al, 2017a , 2017b ; Rosenthal et al, 2019 ; Umberson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 54%
“…A moderate to strong association between relationship satisfaction and dyadic coping was identified in a meta-analytic review of 39 studies (Falconier & Kuhn, 2019 ). This association has also been identified among heterosexual couples coping with health concerns such as cancer, infertility, and organ transplants (e.g., Badr et al, 2010 ; Molgora et al, 2019 ; Tkachenko et al, 2019 ; Van Schoors et al, 2019 ) and similar findings have been identified among partnered SMM in the realm of HIV-related health (Gamarel & Revenson, 2015 ; Martins et al, 2020 ) and non-HIV health concerns (Randall et al, 2017a , 2017b ; Rosenthal et al, 2019 ; Umberson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 54%
“…In distress situations, social support buffers the detrimental effects of stressful events by enhancing self-efficacy, leading to fewer depressive symptoms [31,32]. Several studies also have portrayed that quality support from family is significantly connected with better adjustment to and healing from severe diseases, and with healthier neuroendocrine functioning and good mood [73][74][75][76]. As such, mothers lacking social support will have a harder time enduring the challenges linked with EBF along with the emotional toll connected with a sense of guilt and inadequacy due to early discontinuation of EBF, exaggerating links between EBF termination and PPD.…”
Section: Plos Onementioning
confidence: 99%
“…Couple dyadic adjustment represents the degree to which couples are satisfied with their relationship in domains such as cohesion, satisfaction, consensus, and affective expression (Table 2). Thus, high levels of dyadic adjustment reflect better adjustment and better quality of couple relationship [11,[16][17][18][19][20][21].…”
Section: Family Copingmentioning
confidence: 99%